Phytochemical analysis and biological activities of solvent extracts and silver nanoparticles obtained from Woodwardia unigemmata (Makino) Nakai - Syed Ahsan Shah; Alia Gul; Ghulam Mujtaba Shah; Maha Saeed Ibrahim Wizrah; Awais Khalid; Mamoona Munir; Zainab Maqbool; Arusa Aftab; Mazen R. Alrahili; Ayesha Siddiqua; M. Yasmin Begum (PLoS ONE, 2025)
Multidrug resistant bacteria are causing health problems and economic burden worldwide; alternative treatment options such as natural products and nanoparticles have attained great attention recently. Therefore, we aimed to determine the phytochemicals, antibacterial potential, and anticancer activity of W. unigemmata. Extracts in different organic and inorganic solvents were prepared, silver nanoparticles were prepared using the green synthesis method. Phytochemicals and antioxidant activity was determined spectrophotometry, anticancer potential was determined against gastric cancer and normal gastric epithelial cells using CCK8 and colony formation assays W. unigemmata was found to have a significant enrichment of various phytochemicals including flavonoids, terpenoids, alkaloids, carotenoids, tannins, saponins, quinines, carbohydrates, phenols, coumarins and phlobatanins. Among them phenolics (5289.89 ± 112.67) had high enrichment followed by reducing sugar (851.53 ± 120.15), flavonoids (408.28 ± 20.26) and ascorbic acid (347.64 ± 16.32), respectively. The extracts prepared in organic solvents showed strong antibacterial activity against P. aeruginosa (chloroform, 13.66±0.88, ethyl acetate, 8.66±4.33, methyl alcohol, 13.33±1.66, N-hexane, 12.33±0.88) and S. aureus (chloroform, 15±0.57, ethyl acetate, 16.33±0.33, methyl alcohol, 17.66±0.33 and N-hexane, 16.33±0.33). Aqueously prepared AgNPs showed remarkable activity against P. aeruginosa follwed by E. coli, 17.66 ± 1.85, S. aureus, 16.00 ± 1.73, K. pneumoniae, 14.33 ± 1.20, respectively. The ethanolic extracts (500 μg, 1000 μg, 2000 μg) of the W. unigemmata were found to have cytotoxicity against both gastric cancer (AGS and SGC7901) and normal cell lines (GES-1); a significant cellular proliferation arrest was observed. These results suggest that W. Unigemmata contains numerous bioactive phytochemicals and can be useful as a drug against MDR bacterial strains. These biomolecules covering AgNPs may enhance their biological activities, which can be employed in the treatment of various microbial infections.